Matching logistics delivery services system of H.A.Z Logistics, Shipping and Movers Sdn. Bhd. with expected customers satisfaction - Surani, Suhana (2005)
The globalization of business and the competitive pressure of the business arena have led to growing strategic importance of the logistics function. Many organizations see logistics as the last competitive advantage but this subject is very important to anyone that involved purely in logistics service. In order to achieve customer’s satisfaction, a management needs good strategies, highly motivated employees and a good standard of professional working procedure. In this research, an investigation towards matching logistics delivery service system with expected customer’s satisfaction has been conducted. The objective of the study are (1) To identify the problem associated with delivery service system provide by H.A.Z, (2) To investigate whether H.A.Z delivery service system quality meet its customer’s expectation, and (3) To identify whether the image of HAZ is negatively influenced by word-of-mouth spread by the dissatisfied customers. The service quality model helps in measuring the customers’ satisfaction level. Results indicate that customer satisfaction does play an important role in determining the performance level of services provided by HAZ.